Analisis Kemampuan Membaca Permulaan Siswa Kelas Rendah di SD Negeri 09 Tanjung Lay - Rika Amelia; Peterianus, Septian (JURNAL PENDIDIKAN DAN PEMBELAJARAN SEKOLAH DASAR, 2025)
Abstract: This study aims to analyze the early reading skills of lower-grade students at SD Negeri 09 Tanjung Lay. Early reading is the fundamental stage in the process of learning to read in elementary school, serving as an essential foundation for mastering other language skills. This research employed a qualitative method with a descriptive approach. The subjects consisted of one teacher and 18 first-grade students. Data were collected through observation and interviews focusing on students’ reading abilities. The results showed that out of 18 students, 13 were able to read fluently without spelling out words, while 5 students still faced difficulties in recognizing letters, distinguishing between uppercase and lowercase letters, and remembering words in a text. The main factors contributing to these reading difficulties included delayed letter recognition and limited reading instruction time at school. The teacher played an active role in addressing these challenges through repeated reading activities, providing individualized reading materials, and extending reading practice time. The study concludes that the early reading ability of students at SDN 09 Tanjung Lay is generally good, although more varied teaching strategies and parental involvement are needed to further support students’ reading development. Keywords: Reading Ability, Early Reading, Elementary School Students. Abstrak: Penelitian ini bertujuan untuk menganalisis kemampuan membaca permulaan siswa kelas rendah di SD Negeri 09 Tanjung Lay. Membaca permulaan merupakan tahap dasar dalam proses belajar membaca di sekolah dasar yang menjadi fondasi penting bagi penguasaan keterampilan berbahasa lainnya. Penelitian ini menggunakan metode kualitatif dengan pendekatan deskriptif. Subjek penelitian terdiri atas satu orang guru dan 18 siswa kelas I. Teknik pengumpulan data dilakukan melalui observasi dan wawancara yang berfokus pada kemampuan membaca siswa. Hasil penelitian menunjukkan bahwa dari 18 siswa, 13 siswa telah mampu membaca lancar tanpa mengeja, sedangkan 5 siswa lainnya masih mengalami kesulitan mengenali huruf, membedakan huruf besar dan kecil, serta mengingat kata dalam bacaan. Faktor penyebab utama kesulitan membaca permulaan di antaranya keterlambatan pengenalan huruf dan keterbatasan waktu pembelajaran membaca di sekolah. Guru berperan aktif dalam mengatasi kesulitan tersebut melalui kegiatan membaca berulang, pemberian bahan bacaan individual, serta penambahan jam belajar membaca. Penelitian ini menyimpulkan bahwa kemampuan membaca permulaan siswa di SDN 09 Tanjung Lay tergolong baik, namun masih diperlukan strategi pembelajaran yang bervariasi serta keterlibatan orang tua untuk mendukung keberhasilan siswa dalam belajar membaca. Kata Kunci: Kemampuan Membaca, Membaca Permulaan, Siswa Sekolah Dasar.